Waqaf participation among Muslims in Penang - Nailul Morad Mohd Nor; Mohd Firdaus Zakaria (Proceedings of AICS - Social Sciences, 2013)
Waqaf (Islamic endowment) is one of the socio-economic instruments that can be utilized by the community to develop projects or programs by providing essential economics resources. The significant role of waqaf in the Islamic community development in the past has been acknowledged. However, with the passage of time, the roles of waqaf have been limited and forgotten by most Muslims. A purposive random survey was conducted in the state of Penang, Malaysia to determine their participation in the various forms of waqaf such as cash waqaf, mosques, and schools. The findings indicated that sixty three percent of the Muslims respondents had never participated in any waqaf program.To address the issue of lacking of participation in waqaf, this paper aims to seek the reasons behind this lackadaisical and the roles of the Penang Religious Council in promoting waqaf to the Muslims in Penang. Keywords: Waqaf, cash waqaf, Penang Religious Council